Leadership and Management Development in Education - Bush Tony (Sage Publications, 2008)
This text is essential reading for students of educational leadership and management as well as for policy-makers, headteachers and principals. Preface, Leadership and School Improvement, Models of Educational Leadership, The Significance of Leadership and Management Development, The Curriculum for Leadership Development: Content and Process, Preparing and Supporting Leaders in Developed Countries, The National College for School Leadership, Preparing and Supporting Leaders in Developing Countries, The Impact of Leadership Development, The Future of Leadership Development, References, Author and Subject Index.